Perceptions of Smallholders Farmers on Oil Palm Plantation Cooperative in Kongbeng, East Kutai - Christian Pratama Putra; Dwi Sadono; Djoko Susanto (Jurnal Penyuluhan, 2020)
Farmers' perception toward a program is the primary basis for their willingness to participate in the program. The objectives of the research are: (1) to know the perception level of farmers in the palm oil plantation cooperatives, (2) to analyse the correlation between internal and external factors with farmers perception. The study was conducted on May 2018 in Kongbeng Sub District of East Kutai District. The sample size is 66 farmers who are a member of a cooperative and cultivate palm oil on his land. The analysis used is descriptive statistics and Rank Spearman correlation. The results showed that the perception of farmers about the existence of cooperatives in community palm oil plantations in the form of cooperative benefits and the implementation of cooperatives are in a good category. Internal factors are significantly related to the perception of farmers only at the level of formal education in the benefits of cooperatives. Other internal factors have no relationship with the perception of farmers. Most of the external factors are highly correlated with farmers' perceptions of partnership support, farmer group support, extension support, and local government support.